Probiotics and organic acids as biocontrol agents to optimize embryonic development and hatching of Penaeus vannamei: Probióticos y ácidos orgánicos como biocontroladores para optimizar el desarrollo embrionario y la eclosión de Penaeus vannamei - Velásquez Salcedo, Luis Enrique (2025)
Embryonic development of Penaeus vannamei is susceptible to infections caused by fungi, viruses, and bacteria present in the culture medium or transmitted from broodstock to offspring during spawning. Essential oils, organic acids, natural extracts, prebiotics, and probiotics have often been used to strengthen the immune system and ensure the development of shrimp. To improve the health and viability of nauplii, the efficacy of commercial HGS-7 products containing probiotic bacteria (Bacillus subtilis, Lactobacillus lactis, Nitrosomonas sp. and Nitrobacter sp.) and ACID 5FIVE with organic acids (fumaric, malic, citric, lactic and succinic), applied independently or combined for 20 days in the tanks of gravid females (under standardized parameters) during the spawning and hatching processes. The combination of probiotics and organic acids eliminated Pseudomonas spp. but not Vibrio spp. Fertility rate increased (89.40%), and a lower nauplii deformity rate (0.5%) was observed in the combined treatment. The significant reduction of Pseudomonas through the combination of HGS-7 and ACID 5FIVE provides an effective solution, which successfully promotes embryonic development of P. vannamei. This strategy may improve the efficiency and sustainability of aquaculture production by reducing the bacterial load and improving the viability and egg production rate of P. vannamei.